CMAC-based modelling for HPDDL welding process control. (19th June 2006) - Duan, Peiyong; Zhang, Yu Ming
A Cerebellar Model Articulation Controller- (CMAC-) based modelling method and closed-loop control system were developed to estimate and control the weld fusion for measuring the topside and backside bead widths of the weld pool in High Power Direct Diode Laser (HPDDL) welding. Because of the difficulty in using backside sensor, a topside weld pool geometry is measured using a topside vision sensor and is also used to measure the backside bead width. The drive current of the laser and the welding speed are taken as the control variables. The basic function of CMAC-based steady-state models, which are more easily obtained than dynamic ones, of the non-linear controlled process can predict the control variables with satisfactory accuracy to shorten output response transient time, and two simple Proportional and Integral (PI) controllers are included in the control system to adjust the control variables to maintain outputs at the desired levels. The results of closed-loop control simulations of laser welding process demonstrate that the developed control system is effective and robust to fluctuations or variations that lead to the changing parameters of the non-linear model.